Occult Pneumothoraces in Children With Blunt Torso Trauma. (April 2014) - Lee, Lois K.; Rogers, Alexander J.; Ehrlich, Peter F.; Kwok, Maria; Sokolove, Peter E.; Blumberg, Stephen; Kooistra, Joshua; Olsen, Cody S.; Wootton‐Gorges, Sandra; Cooper, Arthur; Kuppermann, Nathan; Holmes, James F.; et al.
Abstract Objectives Plain chest x‐ray (CXR) is often the initial screening test to identify pneumothoraces in trauma patients. Computed tomography (CT) scans can identify pneumothoraces not seen on CXR ("occult pneumothoraces"), but the clinical importance of these radiographically occult pneumothoraces in children is not well understood. The objectives of this study were to determine the proportion of occult pneumothoraces in injured children and the rate of treatment with tube thoracostomy among these children. Methods This was a planned substudy from a large prospective multicenter observational cohort study of children younger than 18 years old evaluated in emergency departments (EDs) in the Pediatric Emergency Care Applied Research Network (PECARN) for blunt torso trauma from May 2007 to January 2010. Children with CXRs as part of their trauma evaluations were included for analysis. The faculty radiologist interpretations of the CXRs and any subsequent imaging studies, including CT scans, were reviewed for the absence or presence of pneumothoraces. An "occult pneumothorax" was defined as a pneumothorax that was not identified on CXR, but was subsequently demonstrated on cervical, chest, or abdominal CT scan. Rates of pneumothoraces and placement of tube thoracostomies and rate differences with 95% confidence intervals (CIs) were calculated. Results Of 12, 044 enrolled in the parent study, 8, 020 (67%) children (median age = 11.3 years, interquartile range [IQR] = 5.3 to 15.2 years) underwent CXRs in the ED, and these children make up the study population. Among these children, 4, 276 had abdominal CT scans performed within 24 hours. A total of 372 of 8, 020 children (4.6%; 95% CI = 4.2% to 5.1%) had pneumothoraces identified by CXR and/or CT. The CXRs visualized pneumothoraces in 148 patients (1.8%; 95% CI = 1.6% to 2.2%), including one false‐positive pneumothorax, which was identified on CXR, but was not demonstrated on CT. Occult pneumothoraces were present in 224 of 372 (60.2%; 95% CI = 55.0% to 65.2%) children with pneumothoraces. Tube thoracostomies were performed in 85 of 148 (57.4%; 95% CI = 49.0% to 65.5%) children with pneumothoraces on CXR and in 35 of 224 (15.6%; 95% CI = 11.1% to 21.1%) children with occult pneumothoraces (rate difference = –41.8%; 95% CI = –50.8 to –32.3%). Conclusions In pediatric patients with blunt torso trauma, pneumothoraces are uncommon, and most are not identified on the ED CXR. Nearly half of pneumothoraces, and most occult pneumothoraces, are managed without tube thoracostomy. Observation, including in children requiring endotracheal intubation, should be strongly considered during the initial management of children with occult pneumothoraces.